MECHANISMS FOR IMPROVING MANAGEMENT COMPETENCE OF LEADERS IN PRESCHOOL EDUCATIONAL ORGANIZATIONS (American Journal of Interdisciplinary Research and Development, 2024)
This article will provide feedback and feedback on the mechanisms of improving the management competence of the heads of the preschool educational organization. Improving the management competence of heads of preschool educational organizations is crucial for the delivery of high-quality early childhood education. Effective management in these settings not only ensures the smooth operation of daily activities but also plays a pivotal role in fostering an environment conducive to the developmental needs of young children.